Study of stability of periodic aeration algorithm - Mits, N. G.; Beloshenko, K. S.; Bozhkov, A. I. (Biophysical Bulletin, 2021)
Background: The issue of periodic aeration, which can be used as a tool in the process of biological wastewater treatment, has always received undeservedly little attention. Since the optimization of all technological processes in terms of productivity and energy consumption is a matter of time, so, in our opinion, a deeper study and research of physical and biological processes that affect the metabolism of microorganisms during periodic aeration is very important. Objectives of the work are i) determination of conditions of stable state of biocenosis of microorganisms during application of short-cycle periodic aeration regime, ii) drawing up a mathematical model of the aeration system that links the increase in biomass depending on the oxygen concentration, iii) determination of minimum limit concentrations of oxygen and microorganisms as conditions for system stability. Materials and Methods: The aeration system is modeled using a system of differential equations describing the dynamics of reproduction of microorganisms taking into account the supply of oxygen by the aeration system to ensure the metabolism of microorganisms. Experimental studies were carried out in an artificially made laboratory aeration tank (0.7 m´ 0.7 m ´1.2 m, with a volume of 500 liters). Results: The solution of the system of differential equations gave the conditions for the stability of the system, i.e. the limiting concentrations of microorganisms and oxygen per liter of liquid. Taking into account the stability conditions, an equation was derived to determine the threshold level of oxygen concentration at which it is necessary to end the aeration period. With the help of data obtained as a result of laboratory experiments, it became possible to numerically determine the coefficient of residual oxygen content γ, using which it is possible to determine the limiting oxygen concentration. Conclusions: From the systems of differential equations, which consist of the equation of reproduction of microorganisms according to the logistic model and the equation that describes the dynamics of oxygen concentration in the aeration tank liquid, the conditions under which the system has stability are found. From the conditions of stability the equation that sets the condition for shutting off the supply of oxygen to the aeration system in the algorithm of periodic aeration is followed. The optimal degree of purification and the total aeration time in the experiments testify that the interval of concentrations of O2 in the exhaust gases, at which the aeration period should be end, can be determined by this equation, taking the numerical value of the coefficient γ equal to 0.01–0.02.